Dogs in the Sun. - Nyamndi, G. D. (Langaa RPCIG, 2009)
This compelling narrative pits the legacies of two men in the village of Nwemba. Winjala the Crude, yardman to the English surveyor Pete Harrington, kills the latter's favourite animal, the big monkey called Stirrup, and runs to his village. Sama Gakoh, washerman to Harrington, also returns home when his services are terminated for age reasons. Both hold clashing views of the white man. They die shortly after their return but their sons pick up and sustain their conflicting philosophies. The drama culminates in the fishing contest where the village chief, Ndelu, takes an unprecedented decision.